2009
DOI: 10.1007/s12199-009-0098-5
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional relationship between vital capacity and metabolic syndrome and between vital capacity and diabetes in a sample Japanese population

Abstract: Objectives A lower vital capacity (VC) has been reported to be an independent predictor of diabetes in Western countries. The aim of this study was to examine the relationships between VC and diabetes and between VC and metabolic syndrome (MS) in Japanese individuals. Methods Stepwise multiple linear regressions with fasting glucose as a dependent variable and age, metabolic risk factors, and percentage vital capacity (%VC) as independent variables were performed using data obtained from 1651 men and 957 women… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 31 publications
1
13
0
Order By: Relevance
“…The current findings are consistent with previous studies of the association between diabetes and lung function in mainly Caucasian ethnic groups [4,5,18] and Japanese populations [19,20]. Moreover, a recent Korean study reported that restrictive pulmonary dysfunction is independently associated with type 2 diabetes [6].…”
Section: Discussionsupporting
confidence: 92%
“…The current findings are consistent with previous studies of the association between diabetes and lung function in mainly Caucasian ethnic groups [4,5,18] and Japanese populations [19,20]. Moreover, a recent Korean study reported that restrictive pulmonary dysfunction is independently associated with type 2 diabetes [6].…”
Section: Discussionsupporting
confidence: 92%
“…Lung function has proved to be an effective and non-invasive measure of the respiratory health of individual patients and populations. Its assessment not only helps to identify people with a potential risk for COPD, but may also predict survival in asymptomatic adults who do not have chronic respiratory diseases or persistent respiratory symptoms (Burney and Hooper, 2011), as well as in people with numerous other adverse health conditions, including metabolic syndrome (Oda and Kawai, 2009), type 2 diabetes mellitus (Yeh et al, 2005), cardiovascular disease (Johnston et al, 2008), and lung cancer (Mannino et al, 2003). Thus, it is important to identify risk factors that negatively affect lung function in order to enable earlier detection of morbidity.…”
Section: Introductionmentioning
confidence: 99%
“…However, a cross-sectional study of the association between LDL-C and MetS in Japanese men and women found that LDL-C was significantly associated with MetS, especially in the women. 11 Increased serum levels of hs-CRP, increased WBC, increased serum levels of GGT and/or alanine aminotransferase, 12 increased urinary excretion of albumin, 13 increased resting heart rate, 14 and decreased vital capacity 15 are also reported as associated components of MetS. Thus, I propose an extended concept of MetS developing through adipose tissue disease, 10 as shown in Figure. …”
Section: Article P 2258mentioning
confidence: 97%